Maturity Level of Data Management at The Department of Tourism, Youth and Sports - Rifky Akbar Vetian; Anis Lelitasari; Reza Ilyasa; Rangga Gading Satria (Eduvest - Journal of Universal Studies, 2025)
The rapid development of technology and information requires data and information in organizational business processes, including government organizations such as the Tourism, Youth and Sports Agency (Parpora). In realizing its vision, namely, realizing superior tourism, youth and sports achievements build an information system for the management of tourism objects. Where a growing tourism object metadata is needed. Therefore, the Parpora needs to perform data management to solve these problems, it requires good data management. The proposed solution is to build a data governance program. This research is expected to provide recommendations for data management to improve data management in the Department of Parpora by using the DAMA-DMBOK framework so that running business processes can be more effective and efficient in achieving the business strategy of the organization. From the results of measuring the maturity level of data governance using the DAMA-DMBOK framework, it is found that in general, the Parpora Agency is at level 3 or the level, defined which means the stage where the Parpora Agency has standardized the process used to ensure consistency throughout the organization and has carried out documentation and outreach throughout the organization.